An Analysis of Congressional Voting on Legislation Limiting Congressional Campaign Expenditures - Bender, Bruce (Journal of Political Economy, 1988)
Congressional voting on proposed floor amendments concerned solely with setting the level of the election campaign expenditure ceiling provision of the House Administration Committee's broad campaign finance reform bill of 1974 is analyzed for consistency with either the public-interest or economic theories of regulation. The benefit or cost to the individual congressman of a given ceiling is defined as the implied increase or decrease in his probability of reelection under the ceiling. Logit regression analysis provides the preponderant support for the economic theory of regulation by indicating that the likelihood of voting for a given ceiling varies directly with the implied change in reelection probability under the ceiling and is quite sensitive to the implied change.